The influence of soil drying- and tillage-induced penetration resistance on maize root growth in a clayey soil - Li-rong LIN; Yang-bo HE; Jia-zhou CHEN (Journal of Integrative Agriculture, 2016)
Soil drying may induce a number of stresses on crops. This paper investigated maize (Zea mays L.) root growth as affected by drought and soil penetration resistance (PR), which was caused by soil drying and tillage in a clayey red soil. Compared with conventional tillage (C) and deep tillage (D), soil compaction (P) and no-till (N) significantly increased soil PR in the 0–15 cm layer. The PR increased dramatically as the soil drying increased, particularly in soil with a high bulk density. Increased soil PR reduced the maize root mass density distribution not only in the vertical profile (0–20 cm) but also in the horizontal layer at the same distance (0–5, 5–10, 10–15 cm) from the maize plant. With an increase in soil PR in pots, the maize root length, root surface area and root volume significantly decreased. Specifically, the maize root length declined exponentially from 309 to 64 cm per plant with an increase in soil PR from 491 to 3 370 kPa; the roots almost stopped elongating when the soil PR was larger than 2 200 kPa. It appeared that fine roots (<2.5 mm in diameter) thickened when the soil PR increased, resulting in a larger average root diameter. The average root diameter increased linearly with soil PR, regardless of soil irrigation or drought. The results suggest that differences in soil PR caused by soil drying is most likely responsible for inconsistent root responses to water stress in different soils.